A small molecule composed of anthracene and thienothiophene devised for high-performance optoelectronic applications. (September 2015) - Jang, Young Ju; Lim, Byung Tack; Yoon, Soon Byung; Choi, Ho Jun; Ha, Jae Un; Chung, Dae Sung; Lee, Sang-Gyeong
Abstract: An asymmetric small molecule composed of anthracene and alkylated thienothiophene (2-(anthracen-2-yl)-5-hexylthieno[3, 2-b]thiophene) was synthesized via the Suzuki coupling reaction. The thermal stability, photochemical properties, and morphological characteristics were investigated using thermogravimetric analysis, differential scanning calorimetry, cyclic voltammetry, UV–visible spectroscopy, and X-ray diffraction techniques. The compound demonstrated a good thermal stability of 5% at a decomposition temperature of 336 °C. The solution-processed single-crystal transistor, devised with 2-(anthracen-2-yl)-5-hexylthieno[3, 2-b]thiophene, exhibited high performance with a hole mobility of 0.1 cm 2 /Vs. Furthermore, by utilizing the high mobility of 2-(anthracen-2-yl)-5-hexylthieno[3, 2-b]thiophene, we demonstrated its unprecedented high photoresponsivity of 3370 A/W, a finding that can be attributed to the very efficient photoconductive behavior of a single crystal of 2-(anthracen-2-yl)-5-hexylthieno[3, 2-b]thiophene.